2011
DOI: 10.1080/09540121.2011.565031
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study demonstrating effectiveness of targeted education to improve informed consent understanding in AIDS clinical trials

Abstract: Assessing and improving informed consent understanding is equally important as obtaining consent from participants in clinical trial research, but developing interventions to target gaps in participants’ informed consent understanding remains a challenge. We used a randomized controlled study design to pilot test an educational intervention to improve actual informed consent understanding of new enrollees in the Adult AIDS Clinical Trial Group (AACTG). Questionnaires were administered to 24 enrollees to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…Another recent study of a video intervention corroborated this finding [15]. Two recent publications on a targeted educational session and a video intervention to increase participant’s understanding of informed consent without the details of a particular clinical trial did show improved post-training scores in addition to retention of this information [16,17]. …”
Section: Introductionmentioning
confidence: 72%
“…Another recent study of a video intervention corroborated this finding [15]. Two recent publications on a targeted educational session and a video intervention to increase participant’s understanding of informed consent without the details of a particular clinical trial did show improved post-training scores in addition to retention of this information [16,17]. …”
Section: Introductionmentioning
confidence: 72%
“…Wray () randomized cancer patients to a written booklet, tailored brochure, or patient‐specific information, and reported no differences among the groups in terms of comprehension. Sengupta () provided targeted education to improve the understanding of the eight basic elements of informed consent by addressing incorrect answers using the QuIC form (Joffe et al, ) at two different time periods for two groups (Sengupta, ). While the study reported improved understanding from baseline measurement, after 5 weeks, subject understanding waned to less than baseline (Sengupta, ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean ± SD, CS achieved by the participants was 13.4 ± 2.9; median 14 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The highest correct responses were obtained for questions on background details (38%).…”
Section: Nusrat Shafiq Samir Malhotramentioning
confidence: 99%
“…New enrolees in the Adult AIDS Clinical Trial Group (AACTG) were administered to assess their baseline understanding on eight elements of informed consent associated with AIDS clinical trials. 12 Enrollees who scored 85% or less were randomly assigned to in-person, targeted education (intervention) or delayed education (control). Two follow-up assessments were administered.…”
Section: Nusrat Shafiq Samir Malhotramentioning
confidence: 99%